2016
DOI: 10.2298/eka1611029k
|View full text |Cite
|
Sign up to set email alerts
|

Is internal devaluation policy in the EU effective?

Abstract: This research provides indepth analysis of the causes and outcomes of internal devaluation policy in EU. It is conducted using statistical and econometric tools on a sample of three groups of EU member states: EU new member states, PIIGS, and the rest of the EU (EU-core). The analysis points to the key drivers of economic growth in the whole of the EU as being productivity and investment (and consumption in EU new member states and EU core members). Unit labour costs are relevant for GDP grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This outcome may well be an alert for policies that base intra-area adjustment solely on downward price pressures. The conclusion is in line with Villanueva et al (2018), Kersan-Skabi c (2016), and essentially, with Ux o et al ( 2014) as well. Furthermore, it underlines the relevance of non-price factors as highlighted by many authors listed earlier.…”
Section: Relationship Between Adjusted Exports and Price Changessupporting
confidence: 90%
“…This outcome may well be an alert for policies that base intra-area adjustment solely on downward price pressures. The conclusion is in line with Villanueva et al (2018), Kersan-Skabi c (2016), and essentially, with Ux o et al ( 2014) as well. Furthermore, it underlines the relevance of non-price factors as highlighted by many authors listed earlier.…”
Section: Relationship Between Adjusted Exports and Price Changessupporting
confidence: 90%
“…This means that the whole burden of adjustment must be shouldered by the periphery countries. In Bilbao‐Ubillos (2013) several authors warn of the deflationary risk inherent in the strategy of internal devaluation and cast doubt on its effectiveness, interpreting that the double‐dip in the EU in 2011–2012 can be put down to such a self‐inflicted crisis. Tressel et al (2014) highlight how difficult it is to restore the external balance (sustainability of external borrowing) and the internal balance (a level of growth high enough to reduce unemployment) simultaneously: the reduction in domestic demand caused by internal devaluation would need to be more than offset by the increase in external demand. Stockhammer and Wildauer (2016) highlight that in countries such as the UK, Ireland, Spain, Greece and Portugal, households increased their debt to maintain consumption levels in the absence of decent wage increases. Bajo‐Rubio et al (2016) analyse the case for the Southern European members of the euro area (Greece, Italy, Portugal and Spain) and conclude that demand appears to be more relevant than relative prices in explaining the trend in trade flows. Accordingly, to improve the trade balance one needs to place greater trust in an increase in external demand rather than lowering relative prices; at the same time, an improvement in domestic demand might jeopardise any favourable developments in the balance of trade. Kersan‐Škabić (2016) finds that unit labour costs are relevant for GDP growth in (Portugal, Italy, Greece and Spain) but with a positive sign, while for the rest of the EU they are not a significant variable. The policy of internal devaluation is unsuitable for application in any EU member states, due to individual specificities. Bilbao‐Ubillos and Fernández‐Sainz (2019) analyse the case of Spain and do not find a positive link between the trend in cost competitiveness (measured by comparing ULC with competitors) and price competitiveness (estimated via the price of exports). Villanueva et al (2020) focus on the case of Spain and state that the internal devaluation strategy led to a fall in ULC of 3.28 pp between 2010q2 and 2018q4.…”
Section: Theoretical Framework Of the Crisis Exit Strategy: Internal ...mentioning
confidence: 99%
“…Indeed, some authors have suggested alternative crisis management schemes: Eichengreen believed that it was necessary to supplement any exit strategy designed for the periphery with releases from debt: ‘This simple fact creates a fundamental contradiction for the internal devaluation strategy: the more that countries reduce wages and costs, the heavier their inherited debt loads become’ (Eichengreen, 2010, p. 1). Weisbrot and Ray (2011) argue for the adoption of counter‐cyclical fiscal and monetary policies (rather than pro‐cyclical policies such as internal devaluation) accompanied when necessary (e.g. in Latvia) by exchange rate adjustments. Janssen (2013) points out that another force which can contribute positively to the performance of exports is the trend in the nominal effective exchange rate (depreciation of the euro). Gomes et al (2014) defend the idea of a temporary fiscal devaluation, which they define as a combination of two measures: reductions in the social welfare contributions paid by employers and an increase in taxes on consumption. Puglisi (2014) and Farhi et al (2014) both support the fiscal devaluation approach as an alternative policy option for improving competitiveness in the short term by shifting taxation from labour to consumption. Onaran and Stockhammer (2016) defend a strategy of wage‐led growth that would require a mix of policies aimed at predistribution and redistribution as well as macroeconomic policies and industrial policy for full employment and ecological sustainability. Kersan‐Škabić (2016) proposes greater fiscal cooperation (transfers) and a rethinking of the ECB policy of price stability. Mariolis et al (2019) call for a wider, more flexible strategy framework that includes an intra‐Eurozone industrial, trade and currency depreciation policy on the one hand and per country‐ and sector‐specific wage rate changes and demand management policies on the other. Xifré (2020) maintains that, in economic terms, applying internal devaluation intensively as a general‐purpose, open‐ended solution may jeopardise the ability of euro zone periphery firms to compete internationally by undermining non‐price/cost factors, which play a vital role in supporting competitiveness. …”
Section: Theoretical Framework Of the Crisis Exit Strategy: Internal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…These immediate recessionary effects and vicious circles have prompted research to evaluate the outcome of the recent internal devaluation efforts of some eurozone members. Examples include Anastasatos 2011, 2013;Uxó et al 2014;Kersan-Škabić 2016;Villanueva et al 2018). Most of them are understandably concerned with austerity measures forced by EU-IMF creditors as a no-other-way policy.…”
Section: Risk Mitigation By Price Adjustment?mentioning
confidence: 99%